Biochemical screening and antibacterial activates of selected medicinal plants from District Harnai, Balochistan Pakistan - Bibi, Tahira; Tareen, Niaz Muhammad; Channa, Farah Naz; Behlil, Farida; Jamil, Nelofer; Sajjad, Naheed; Irfan, Shazia; Mengal, Samina; Masood, Ayeesha; Khan, Nazima Yousaf (Journal of Neonatal Surgery, 2025)
This study aimed to carry out the phytochemical and antibacterial activities of the selected medicinal plants from Harnai Balochistan Pakistan. The qualitative and quantitive phytochemical investigation was carried out in four different solvents ethanol, methanol, acetone and chloroform for selected medicinal plant (Olea ferruginea, Tulipa lehmanniana, Pistacia khinjuk and Bunium persicum) and the antimicrobial activity against multi drug resistant strains and environmentally collected strains were carried out. The qualitative phytochemicals finding shows the presence of flavonoids, sugar, protein, phenolic compounds, terpenoids, tannins, cardiac glycerides, steroids, alkaloids, amino acids uniformly in all plants species in all four solvent extracts, glycosides are present in all four species with acetone solvent extracts and is absent in Tulipa lehmanniana, Pistacia khinjuk and Olea ferruginea with chloroform solvent extract and also with ethanol extract in Tulipa lehmanniana and Pistacia khinjuk and it is also absent in Pistacia khinjuk with methanol extracts. Anthroquinone is absent in Tulipa lehmanniana, Pistacia khinjuk and Bunium persicum with chloroform extract but are present in the rest of all extract solvent in all species, fixed oil and saponins is only absent in Tulipa lehmanniana with methanol extract and in Olea ferruginea with ethanol extract solution while it is present with all the rest of solution extract in all sour selected plant species. The quantitative biochemical investigation revealed that the contents of carbohydrates was reported in Bunium persicum 2.83 μg/mg in the methanol solution, the highest Phenolic contents is quantified in Tulipa lehmanniana in the chloroform extract i.e. 16.25 μg/mg extracts, Tulipa lehmanniana have the highest percentage of alkaloids in the methanol extracts (41.2%) Olea ferruginea have the highest percentage of saponins in the ethanol extracts (15.2%) and all the extracts. Bunium persicum have the highest percentage of Proteins in the ethanol extract (10.4 μg/ml) followed by Tulipa lehmanniana with (7.2 μg/ml) in the ethanol extracts Solution. The antibacterial activity of the chloroform extracts of Tulipa lehmanniana shows a very good activity against Staphylococcus aureus (MDR) and Escherichia coli bacteria, the acetone extracts of Tulipa lehmanniana has also shown very good activity against Bacillus brevis bacteria. The ethanolic, methanolic, acetone and chloroform extracts of Pistacia khinjuk have showed moderate activity against Staphylococcus aureus (MDR). It is concluded that the medicinal plants wealth of the area should be further investigated for clinical and pharmaceutical potential in order to natural drug discovery development at regional and global level